The Significance of Emphasis through Conditional Sentences and Their Responses: An Applied Grammatical Study of Surah Al-Baqarah - Sudani Hussein, Assist. Lect. Ahmed (Basra studies journal, 2024)
This study explores the significance of the conditional style and its response through an analysis of Surah Al-Baqarah. The theoretical section introduces the concepts of style, emphasis, condition, and response, along with associated grammatical issues. Surah Al-Baqarah serves as a rich source for the applied analysis, where the researcher examines several key issues related to the conditional style, such as the use of "in" (إنْ) and "whenever" (كلما), the conjunction of the conditional response with "fa" (فَ), and issues of ellipsis and conjunction. These are explored by clarifying the syntactic implications and connecting them to the views of interpreters and grammarians.